2014
DOI: 10.1371/journal.pone.0097873
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Clock Drawing Test (CDT) Performance before and after Cognitive Decline

Abstract: BackgroundMany scoring systems exist for clock drawing task variants. However, none of them are reliable in evaluating longitudinal changes of cognitive function. The purpose of this study is to create a simple yet optimal scoring procedure to evaluate cognitive decline using a clinic-based sample.MethodsClock-drawings from 121 participants (76 individuals with no dementia and later did not develop dementia after a mean 41.2-month follow-up, 45 individuals with no dementia became demented after a mean 42.3-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…The scoring systems share commonalities, but each may reflect different cognitive components and be correlated with different areas of brain atrophy [58]. However, independently from the scoring procedure, performance on CDT in demented patients seems to be inversely correlated with lesion load in medial temporal lobe, in subcortical structures and in periventricular white matter [59,60] and might provide prognostic information for cognitive decline [61,62]. Some authors suggested that qualitative analysis of errors in clock drawing might improve diagnostic accuracy for dementia screening.…”
Section: Drawing Tasks Frequently Used In Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…The scoring systems share commonalities, but each may reflect different cognitive components and be correlated with different areas of brain atrophy [58]. However, independently from the scoring procedure, performance on CDT in demented patients seems to be inversely correlated with lesion load in medial temporal lobe, in subcortical structures and in periventricular white matter [59,60] and might provide prognostic information for cognitive decline [61,62]. Some authors suggested that qualitative analysis of errors in clock drawing might improve diagnostic accuracy for dementia screening.…”
Section: Drawing Tasks Frequently Used In Dementiamentioning
confidence: 99%
“…Poor performance on CDT might predict future development of AD in patients with MCI [98], but not all qualitative scoring procedures might be sufficiently sensitive to capture longitudinal changes of CDT from MCI to AD [61]. A recent metaanalysis [99] confirmed that the CDT might reveal a useful measure of cognitive decline over time, and that conceptual clock drawing errors (with particular mention of hand and number placement) would be most informative about the cognitive decline.…”
Section: Drawing Disorders In Prodromic (Amci) and Clinical Forms Of Admentioning
confidence: 99%
“…The steps of how patients drew the clocks were recorded by the examiner. The results were analyzed according to the 30-point system [22,23]: the first step of CDT is to anchor the "12-3-6-9" on the clock, which is referred to as "30-point system-A (Anchoring) part" (CDT-A, a total of 4 points), and the rest 26 points consist of 13 items to reflect the drawing results, which was called "30-point system-C (Clockface) part" (CDT-C, a total of 26 points). The CDT-A is closely correlated with memory function, while the CDT-C reflects visuospatial and executive function [22].…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…Authors have indicated that deficits in executive functions may be detected earlier than those in memory tasks, irrespective of whether subjects report cognitive complaints. Executive functions are the ability to plan, judge, reason, solve problems and organize; and attention, abstraction and mental flexibility play pivotal roles in executive control . Impairment in executive function predicts Alzheimer's disease and vascular dementia …”
mentioning
confidence: 99%
“…Executive functions are the ability to plan, judge, reason, solve problems and organize; and attention, abstraction and mental flexibility play pivotal roles in executive control . Impairment in executive function predicts Alzheimer's disease and vascular dementia …”
mentioning
confidence: 99%